From Open Dumping to Circular Economy: Institutional Challenges in Solid Waste Governance in Tangerang Regency, Indonesia - Syamsoe Astra Negara; Effie Tristinawati; Alya Nurayu Sulisman; Christianto Deni Saputro; Yugni Maulana Aziz; Jaka Permana (Journal of Social Work and Science Education, 2026)
Rapid urbanization within the Jabodetabekpunjur agglomeration has intensified solid waste management challenges in peri-urban regions such as Tangerang Regency, Indonesia. This study analyzes sustainable solid waste governance in Tangerang Regency, focusing on institutional coordination, integrated waste services, and contributions to urban resilience. Using a descriptive qualitative approach, data were collected through policy document analysis, government reports, academic literature, and observational notes from official forums (2024-2026). Analysis employed thematic synthesis organized around three dimensions: institutional governance, service integration, and resilience building. Key findings reveal: (1) Tangerang Regency generates approximately 2,515 tons of waste daily (0.71 kg/person/day), with non-household sources contributing 66% of total waste; (2) service coverage reaches 87%, yet only 60% of generated waste is transported to final disposal facilities; (3) the Jatiwaringin landfill has less than 5 hectares of remaining capacity from its original 33 hectares; (4) institutional fragmentation, limited waste segregation (only 34% household waste), and reliance on open dumping practices have led to a national “waste emergency” designation (Ministerial Decree No. 2567/2025). The study concludes that sustainable waste governance requires transformation from disposal-oriented to circular economy systems, supported by interregional coordination, green financing mechanisms (including carbon credits), and inclusive participation of formal and informal actors. Limitations include single-region focus and reliance on secondary data. Implications for policy emphasize the urgency of upstream waste reduction, segregated collection systems, and metropolitan-scale governance coordination.